Evaluating host diet effects on microparasites by measuring the stoichiometry of infrapopulations one cell at a time - Charlotte F. Narr; Scott Binger; Erin Sedlacek; Bianca Anderson; Grace Shoemaker; Adrienne Stanley; Madison Stokoski; Ed Hall (Ecology and Evolution)
Abstract Progress in the field of ecological stoichiometry has demonstrated that the outcome of ecological interactions can often be predicted a priori based on the nutrient ratios (e.g., carbon: nitrogen: phosphorus, C:N:P) of interacting organisms. However, the challenges of accurately measuring the nutrient content of active parasites within hosts has limited our ability to rigorously apply ecological stoichiometry to host–parasite systems. Traditional nutrient analyses require high parasite biomasses, often preventing individual‐level analyses. This prevents researchers from estimating variation in the nutrient content of individual parasites within a single host infrapopulation, a critical factor that could define how the ecology of the parasite affects the host–parasite interaction. Here, we explain how energy dispersive technology, a technique currently used to measure the elemental content of free‐living microbes, can be adapted for parasitic microbial infrapopulations. We demonstrate the power of accurately quantifying the biomass stoichiometry of individual microbial parasites sampled directly from individual hosts. Using this approach, we show that the stoichiometric composition of two microbial parasites capable of infecting the same host are stoichiometrically distinct and respond to host diet quality differently. We also demonstrate that characteristics of the stoichiometric trait distributions of these infrapopulations were important predictors of host fecundity, a proxy for virulence in this system, and better predictors of parasite load than the mean parasite stoichiometry or our parasite and diet treatments alone. EDS provides a rigorous tool for applying ecological stoichiometry to host–parasite systems and enables researchers to explore the nutritional physiology of host–parasite interactions at a scale that is more relevant to the ecology and evolution of the system than traditional nutrient analyses. Here we demonstrate that this level of resolution provides useful insights into the diet‐dependent physiology of microbial parasites and their hosts. We anticipate that this improved level of resolution has the potential to elucidate a range of eco–evo interactions in host–parasite systems that were previously unobservable.